A fully coupled hydrodynamic-DEM model for simulating debris dynamics and impact forces. (1st July 2022) - Xiong, Yan; Liang, Qiuhua; Zheng, Jinhai; Stolle, Jacob; Nistor, Ioan; Wang, Gang
Abstract: Many post-event field investigations suggest that dramatic flood hydrodynamics and impact of large floating objects contribute significantly to building damage during a tsunami event. However, the interactions between the transient flood waves, floating debris, and structures have neither been well explored nor understood, and few modelling tools have been developed to simulate these complex interactive processes, especially when multiple debris are involved. This paper introduces a novel fully coupled modelling system, based on a high-performance 2D hydrodynamic model and a 3D discrete element method (DEM) model, for simulating the movement of multiple debris carried along by highly convective flows and directly quantifying the induced impact forces on structures. The proposed model is applied to reproduce a series of physical experiments, and the results agree well with the experimental measurements. It is demonstrated that the newly coupled modelling system can capture the interaction between the fluid, debris of different shapes and sizes and structures, making it suitable for real-world applications. The model provides a new robust tool for simulating the extreme hazards caused by tsunamis or flash flooding and assessing their risk, and therefore has the potential to be useful for planning and designing disaster risk reduction schemes in those at-risk areas. Highlights: A new coupled model for simulating debris transported by transient flood waves. MSM is implemented to represent floating objects of different sizes and shapes. A new approach to estimate the impact forces induced by debris on structures. The model reliably predicts occurring time and magnitude of the peak impact forces.